2019
DOI: 10.1248/bpb.b19-00244
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Agents, Polymethoxylated Flavones Isolated from <i>Kaempferia parviflora</i> for Cataract Prevention through Inhibition of Matrix Metalloproteinase-9 in Lens Epithelial Cells

Abstract: Natural flavonoids have powerful antioxidant activity and have been reported to show promising protective effects against cataracts. The plant Kaempferia parviflora (K. parviflora) is indigenous to southeast Asia, including Thailand, and typically contains polymethoxylated flavones. The flavones in K. parviflora are reported to have various biological properties. Recently, polymethoxylated flavones of K. parviflora (KPMFs) were shown to have potent Sirtuin 1 enzyme-stimulating and anti-glycation activities tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…In addition, Miyata et al found that upregulation of ASC could significantly inhibit the progression of cancer. 25 Our research found ASC was activated in MCF-7 cells in the presence of nobiletin, which further verified that ASC may play a key role in the pyroptosis and apoptosis of MCF-7 and BT-549 cells.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, Miyata et al found that upregulation of ASC could significantly inhibit the progression of cancer. 25 Our research found ASC was activated in MCF-7 cells in the presence of nobiletin, which further verified that ASC may play a key role in the pyroptosis and apoptosis of MCF-7 and BT-549 cells.…”
Section: Discussionsupporting
confidence: 79%
“…At the same time, MAPK inhibitors, specifically for ERK1/2, p38, and JNK, inhibited MMP-9 expression and its subsequent activity in SRA01/04 cells [120]. The PMFs also inhibited phosphorylation of p38 and JNK in SRA01/04 cells, indicating that these flavones regulate MMP-9 mRNA expression via the PKC/p38 and PKC/JNK pathways in LECs [120]. Considering the crucial role of MMP-9 expression in cataract formation such as ASC and PCO, the authors suggested that the dietary intake of PMFs may have a therapeutic potential to prevent or help in the treatment of fibrotic cataracts.…”
Section: Polyphenols and Mmp-9 Inhibitionmentioning
confidence: 88%
“…Considering that MAPK signaling is a crucial mechanism to regulate the expression of MMP, the study showed that PMA increased MAPKs phosphorylation in LECs. At the same time, MAPK inhibitors, specifically for ERK1/2, p38, and JNK, inhibited MMP-9 expression and its subsequent activity in SRA01/04 cells [120]. The PMFs also inhibited phosphorylation of p38 and JNK in SRA01/04 cells, indicating that these flavones regulate MMP-9 mRNA expression via the PKC/p38 and PKC/JNK pathways in LECs [120].…”
Section: Polyphenols and Mmp-9 Inhibitionmentioning
confidence: 94%
“…It was found to increase MMP-2 production in the aqueous humor, reduce IOP and improve the morphology of the trabecular meshwork and retina in rats with steroid-induced glaucoma [203,204]. Miyata and co-workers showed that individual polymethoxylated flavones isolated from Kaempferia parviflora decreased gelatinase activity and the mRNA expression of MMP-9, and increased the protein production of TIMP-2 in phorbol 12-myristate 13-acetate-stimulated LECs via suppression of p38 MAPK, JNK1/2 and ERK1/2 pathway activation [205]. This finding highlights the efficacy of flavones in the prevention of PCO.…”
Section: Natural Agentsmentioning
confidence: 99%